Atypical Cervical Stromal Cells Masquerading as Malignancy - Kurekar, Shraddha Avinash; Chaudhari, Jayashri Popat; Shenoy, Asha Sharad; Chaturvedi, Rachana Amit (Annals of Pathology and Laboratory Medicine, 2021)
Atypical stromal cells (ASCs) of the female genital tract are uncommon and found in various polypoid lesions of the vulva, vagina, cervix and endometrium. Although they are benign; they can be misinterpreted as a malignant. Hence it is important for a pathologist to identify the ASCs in the specimens or biopsies of lower Female genital tract and avoid over diagnosis as a malignancy. We present a case of atypical cervical stromal cells in a 45-year-old female. On microscopy, Atypical stromal cells were stellate, enlarged in size, with moderate to severely atypical hyperchromatic, multilobulated nuclei without any mitoses. Their chromatin was dense often with prominent nucleoli. This report highlights the significance of awareness about the occurrence of these cells in the female reproductive tract.